Avapritinib in advanced PDGFRA D842V-mutant gastrointestinal stromal tumour (NAVIGATOR): a multicentre, open-label, phase 1 trial. Issue 7 (July 2020) - Heinrich, Michael C; Jones, Robin L; von Mehren, Margaret; Schöffski, Patrick; Serrano, César; Kang, Yoon-Koo; Cassier, Philippe A; Mir, Olivier; Eskens, Ferry; Tap, William D; Rutkowski, Piotr; Chawla, Sant P; et al.
Summary: Background: Targeting of KIT and PDGFRA with imatinib revolutionised treatment in gastrointestinal stromal tumour; however, PDGFRA Asp842Val (D842V)-mutated gastrointestinal stromal tumour is highly resistant to tyrosine kinase inhibitors. We aimed to assess the safety, tolerability, and antitumour activity of avapritinib, a novel KIT and PDGFRA inhibitor that potently inhibits PDGFRA D842V, in patients with advanced gastrointestinal stromal tumours, including patients with KIT and PDGFRA D842V-mutant gastrointestinal stromal tumours (NAVIGATOR). Methods: NAVIGATOR is a two-part, open-label, dose-escalation and dose-expansion, phase 1 study done at 17 sites across nine countries (Belgium, France, Germany, Poland, Netherlands, South Korea, Spain, the UK, and the USA). Patients aged 18 years or older, with an Eastern Cooperative Oncology Group performance status of 2 or less, and with adequate end-organ function were eligible to participate. The dose-escalation part of the study included patients with unresectable gastrointestinal stromal tumours. The dose-expansion part of the study included patients with an unresectable PDGFRA D842V-mutant gastrointestinal stromal tumour regardless of previous therapy or gastrointestinal stromal tumour with other mutations that either progressed on imatinib and one or more tyrosine kinase inhibitor, or only received imatinib previously. On the basis of enrolment trends, ongoing review of study data, and evolving knowledge regarding the gastrointestinal stromal tumour treatment paradigm, it was decided by the sponsor's medical director together with the investigators that patients with PDGFRA D842V mutations would be analysed separately; the results from this group of patients is reported in this Article. Oral avapritinib was administered once daily in the dose-escalation part (starting dose of 30 mg, with increasing dose levels once daily in continuous 28-day cycles until the maximum tolerated dose or recommended phase 2 dose was determined; in the dose-expansion part, the starting dose was the maximum tolerated dose from the dose-escalation part). Primary endpoints were maximum tolerated dose, recommended phase 2 dose, and safety in the dose-escalation part, and overall response and safety in the dose-expansion part. Safety was assessed in all patients from the dose-escalation part and all patients with PDGFRA D842V-mutant gastrointestinal stromal tumour in the dose-expansion part, and activity was assessed in all patients with PDGFRA D842V-mutant gastrointestinal stromal tumour who received avapritinib and who had at least one target lesion and at least one post-baseline disease assessment by central radiology. This study is registered with ClinicalTrials.gov, NCT02508532 . Findings: Between Oct 26, 2015, and Nov 16, 2018 (data cutoff), 46 patients were enrolled in the dose-escalation part, including 20 patients with a PDGFRA D842V-mutant gastrointestinal stromal tumour, and 36 patients with a PDGFRA D842V-mutant gastrointestinal stromal tumour were enrolled in the dose-expansion part. At data cutoff (Nov 16, 2018), 38 (46%) of 82 patients in the safety population (median follow-up of 19·1 months [IQR 9·2–25·5]) and 37 (66%) of the 56 patients in the PDGFRA D842V population (median follow-up of 15·9 months [IQR 9·2–24·9]) remained on treatment. The maximum tolerated dose was 400 mg, and the recommended phase 2 dose was 300 mg. In the safety population (patients with PDGFRA D842V-mutant gastrointestinal stromal tumour from the dose-escalation and dose-expansion parts, all doses), treatment-related grade 3–4 events occurred in 47 (57%) of 82 patients, the most common being anaemia (14 [17%]); there were no treatment-related deaths. In the PDGFRA D842V-mutant population, 49 (88%; 95% CI 76–95) of 56 patients had an overall response, with five (9%) complete responses and 44 (79%) partial responses. No dose-limiting toxicities were observed at doses of 30–400 mg per day. At 600 mg, two patients had dose-limiting toxicities (grade 2 hypertension, dermatitis acneiform, and memory impairment in patient 1, and grade 2 hyperbilirubinaemia in patient 2). Interpretation: Avapritinib has a manageable safety profile and has preliminary antitumour activity in patients with advanced PDGFRA D842V-mutant gastrointestinal stromal tumours. Funding: Blueprint Medicines.